Political and Social Issues Impacting on the Theme of Contemporary Poetry - Vafa, Majid Reza Khazaei; Amirahmadi, Abolghasem; Sardehi, Ali Eshghi (Journal of History Culture and Art Research, 2017)
Islamic Revolution has been a significant cultural event in Iran and world. This cultural-social phenomenon has considerably affected all political, social, economic, and cultural aspects of society. The question is that how is this effect on literature and contemporary poetry and has it had effect or not? This study elaborates that entrance of new religious contents, impressionability of ritual poetry, new thinking with religious-social approach in contemporary poetry as well as a new attitude toward death in frame of martyr and martyrdom, and etc. are achievements of revolution in scope of literature. Also, Islamic Revolution could change poetic forms so that modern poetry (free verse) and white poetry (blank verse) can be seen in poems of poets at early years of revolution. This paper argues that Islamic Revolution made the poetry completely social by removing personal aspects and bringing it to community.